2006
DOI: 10.1360/cjcp2006.19(2).102.7
|View full text |Cite
|
Sign up to set email alerts
|

Review of Kelvin's Equation and Its Modification in Characterization of Mesoporous Materials

Abstract: Physical and mathematical models as well as calculation methods of nitrogen bed on porous media have been introduced to evaluate the structural parameters of mesoporous materials. Kelvin's equation is a link between the relative adsorbate pressure, the mean pore radius, and pore capillarity on the basis of macroscopic capillary condensation. However, Kelvin's equation has been identified that it underestimates the calculated pore size of a material especially in the boundary of pore size which is between 2 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…A model-independent Barrett–Joyner–Halenda (BJH) fit to the desorption branch yielded a pore size of 25.0 Å and a pore volume of 0.21 cc/g, which matches extremely well with the modeled structure (Figure S1). This high N 2 uptake confirms the porosity of the COF (Figure A). Drastic lowering of the N 2 uptake is witnessed upon loading the nanoparticles (Figure B).…”
Section: Resultssupporting
confidence: 56%
“…A model-independent Barrett–Joyner–Halenda (BJH) fit to the desorption branch yielded a pore size of 25.0 Å and a pore volume of 0.21 cc/g, which matches extremely well with the modeled structure (Figure S1). This high N 2 uptake confirms the porosity of the COF (Figure A). Drastic lowering of the N 2 uptake is witnessed upon loading the nanoparticles (Figure B).…”
Section: Resultssupporting
confidence: 56%
“…The majority of literature employs the BJH method [33] for determination of pore diameter and pore size distribution. It was observed that the BJH method and related approaches, based on the modified Kelvin equation, underestimate the pore size up to 25% for pores smaller than 10 nm [34]. In this case, the density functional approach was found to provide reliable values for pore diameter and pore size distribution.…”
Section: Nitrogen Sorption Isothermsmentioning
confidence: 93%
“…The classical method of BJH cannot describe the sorption and phase behavior of fluids in narrow mesopores (for widths < 100 Å) correctly, leading to an underestimation of the pore diameters [34]. Rather, a density functional theory (DFT) [35,36] based analysis appears as the most accurate method for pore size and pore size distribution determination.…”
Section: Sorption Analysismentioning
confidence: 99%
“…However, the original model fails to take into account the adsorbed film thickness formed on pore walls. The Cohan's model [50] came up with a modified Kelvin's equation describing capillary condensation with consideration of adsorbed film for an open-ended cylindrical pore. According to this model, the meniscus between the adsorbed film and vapor is cylindrical at capillary condensation for an infinite cylindrical pore:…”
Section: Nitrogen Adsorptionmentioning
confidence: 99%